Man & machine: Adaptive tools for the contemporary performance analyst - Robertson, S. (Journal of Sports Sciences, 2020)
Sport, like many industries, is experiencing growth in resources, professionalism and data generation. An understanding of how humans can effectively and efficiently interact with technology, computers and other machines to improve sports performance is still being developed. As a consequence, the landscape in which the performance analyst now finds themselves has fundamentally changed. New, improved and different skill sets are now required in order to be impactful and experience sustained success. However, this growth also presents new opportunities to address difficult problems, including many that were previously considered intractable. This article lists ten essential adaptive tools for the contemporary performance analyst, many of which are useful in both research and applied sporting environments. A rationale for each is proposed, with an emphasis on ensuring that the performance analyst will be equipped to thrive in both current and future sport environments